Identifikasi Cendawan pada Kacang Tanah Impor (Arachis Hypogea L.) Menggunakan Metode Washing dan Blotter Test: Identifikasi Cendawan pada Kacang Tanah Impor (Arachis Hypogea L.) Menggunakan Metode Washing dan Blotter Test - Hutabarat, Erikantona; Hutajulu, Angel Cristin; Husna, Adibatul; Putri, Nur Aziza; Anggreini, Anggel; Hasibuan, Riski; Manalu, Mayesti (UNIB Press, 2025)
Groundnut (Arachis hypogaea L.) is a cultivated plant that belongs to the Fabaceae family. One of the diseases that commonly attack peanuts is fungus. Fungi are one of the microbial organisms that are found in the soil and the attack carried out by fungi is through plant roots. Infections in peanuts are generally caused by fungi including Alternaria sp, Aspergillus sp, Deshlera sp, Fusarium sp, Mucor sp, Penicillium sp, Rhizoctonia sp, Stemphylium sp, Trichothecium sp. and Verticillium sp. Isolation of pathogenic fungi in peanut seeds was carried out using the International Seed Testing Association (ISTA 1996) standard seed health testing method consisting of washing and blotter test methods. This research conducted on the identification of fungi, the results obtained were Rhizoctonia sp. Aspergillus sp. and Fusarium sp. Based on the research that has been done, the three types of fungi obtained are not included in the Quarantine Plant Disturbing Organisms, but are classified as Ordinary Plant Disturbing Organisms and the use of the Washing test and Blotter test method can be one way to identify the type of fungus in peanuts.